Pengaruh Suku Bunga BI, Inflasi dan Tingkat Kurs terhadap Profitabilitas Bank BCA - Muhammad Rizky Panjaitan; Mangasi Sinurat; Willy Cahyadi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study aims to examine the impact of the BI Rate, inflation, and the exchange rate on the profitability (ROA) of Bank BCA. An associative quantitative approach was employed using a dynamic Ordinary Least Squares (OLS) model that incorporates lagged dependent variables to account for profitability persistence (Yt-4) and quarterly seasonality (Yt-4). Quarterly data obtained from Bank Indonesia (BI) and Badan Statistik Indonesia (BPS) were used for the analysis. The results indicate that the three variables collectively explain 85.12% of the variation in Bank BCA's ROA; specifically, the BI-Rate (X1) has a significant positive effect on ROA, inflation has a significant negative effect on ROA, and the exchange rate has a positive but statistically insignificant effect on ROA. Furthermore, the two lagged variables confirm strong profitability persistence and seasonality, thereby validating the dynamic model specification.